Adaptations et ajustements des gestes professionnels pendant la pandémie chez les enseignants en IUT - Anita Messaoui; Cécile Redondo
Our study analyzes the postures and professional gestures of teachers at a university institute of technology during the transition to distance learning during the covdi-19 pandemic. The analysis of professional practices revolves around the notions of the multi-agenda of teacher action, adjustment and instrumental genesis, from a corpus made up of five interviews with teachers and textual exchanges on the platform Discord. Faced with the obligation of remote teaching mediated by digital technology, scaffolding, control, and accompaniment postures have been favored. The adjustments are also visible in the appropriation processes of the Discord platform.